The dynamics of interleukin‐8 and its interaction with human CXC receptor I peptide. (12th February 2014) - Kendrick, Agnieszka A.; Holliday, Michael J.; Isern, Nancy G.; Zhang, Fengli; Camilloni, Carlo; Huynh, Chi; Vendruscolo, Michele; Armstrong, Geoffrey; Eisenmesser, Elan Z.
Abstract Interleukin‐8 (CXCL8, IL‐8) is a proinflammatory chemokine important for the regulation of inflammatory and immune responses via its interaction with G‐protein coupled receptors, including CXC receptor 1 (CXCR1). CXCL8 exists as both a monomer and as a dimer at physiological concentrations, yet the molecular basis of CXCL8 interaction with its receptor as well as the importance of CXCL8 dimer formation remain poorly characterized. Although several biological studies have indicated that both the CXCL8 monomer and dimer are active, biophysical studies have reported conflicting results regarding the binding of CXCL8 to CXCR1. To clarify this problem, we expressed and purified a peptide (hCXCR1pep) corresponding to the N‐terminal region of human CXCR1 (hCXCR1) and utilized nuclear magnetic resonance (NMR) spectroscopy to interrogate the binding of wild‐type CXCL8 and a previously reported mutant (CXCL8M) that stabilizes the monomeric form. Our data reveal that the CXCL8 monomer engages hCXCR1pep with a slightly higher affinity than the CXCL8 dimer, but that the CXCL8 dimer does not dissociate upon binding hCXCR1pep. These investigations also showed that CXCL8 is dynamic on multiple timescales, which may help explain the versatility in this interleukin for engaging its target receptors.